A retrospective clinical study of 98 adult idiopathic primary intraventricular hemorrhage cases. Issue 42 (October 2016) - Guo, Rui; Ma, Lu; Shrestha, Bal Krishna; Yu, Zhiyuan; Li, Hao; You, Chao
Abstract : Abstract: The aim of the study is to define the clinical features, risk factors, treatment and prognosis of idiopathic primary intraventricular hemorrhage (IPIVH). We retrospectively collected the data of consecutively admitted patients who were diagnosed and treated for IPIVH in our hospital from January 2010 to December 2014. The clinical information, treatment, and prognosis at the 6-month follow-up were analyzed. Among the 3798 cases of spontaneous intracranial hemorrhage (ICH), 98 IPIVH (2.58%) patients were recruited for the study. The study population consisted of 60 males and 38 females, with an average age (± standard deviation, SD) of 51.20 ± 15.48 years. The initial symptoms were headache (75 cases) and impaired consciousness (23 cases). The surgical treatments included hematoma evacuation under a microscope or an endoscope in 8 cases (8.16%), external ventricular drainage (EVD) in 11 cases (11.22%), lumbar drainage (LD) in 10 cases (10.20%), and a combination of EVD and LD in 11 cases (11.22%). In total, 4 patients died in the hospital (4.08%). At the 6-month follow-up, 73 patients (74.49%) had an improved outcome (modified Rankin scale [mRS] < 3), and 21 patients (21.43%) had a poor outcome (mRS ≥ 3 points) at the end of the 6-month follow-up. IPIVH is rare in clinical practice, and hypertension is the most common risk factor. Furthermore, the treatment of IPIVH is still controversial. Hematoma evacuation under a microscope or an endoscope, EVD, LD and a combination of EVD and LD could be surgical options for the treatment of IPIVH patients. The outcomes for IPIVH patients could be relatively favorable with individualized treatment.